The role of public management in Hospital Social Responsibility (HSR) activities in building the image of Sunan Kudus Islamic Hospital - Lailyah, Nurzahroh (Prodi Magister Ekonomi Syariah FEBI UIN Walisongo Semarang, 2020)
Purpose – The purpose of this research is to understand the role of Public Relations Management in activities Hospital Social Responsibility (HSR) to improve image of Sunan Kudus Islamic Hospital. This study is also designed to understand the ability of Hospital Social Responsibility (HSR) in bringing benefits to the hospital Islam Sunan Kudus.Method – Primary data were obtained directly from observations and interviews with the Sunan Kudus Islamic Hospital, in this case the Public Relations Management and the community involved in HSR activities. The data analysis technique used several analyzes, namely descriptive, sociological, hostoris, and data validity.Result – The role of Public Relations in HSR activities can improve image of the Sunan Kudus Islamic Hospital, this is proven with the HSR activities carried out by RSI Sunan Kudus followed by all levels of society in the city Kudus so that through the HSR activity the name RSI Sunan Kudus is known to the wider community and ultimately society who is in the Kudus city to entrust his health to Sunan Kudus Islamic Hospital.Implication – This study can motivate other hospitals to implement HSR (Hospital Social Responsibility), so that a mutual symbiotic relationship can be created between the hospital and the community.Originality – In other studies only discussing CSR in general, there are no findings regarding HSR, and there is no CSR or HSR aspect in it Islamic perspective, apart from that there are no other benefits seen due to the existence of CSR in the hospital